Psychosocial risks and the health of health workers: reflections on Brazilian labor reform - Leni de Lima Santana; Leila Maria Mansano Sarquis; Fernanda Moura D' Almeida Miranda
ABSTRACT Objective: to reflect on the psychosocial risks and their impacts on the health of health workers in light of the Brazilian economic context and Labor Reform. Method: reflective study on the Brazilian Labor Reform and its impacts on health of health workers. Results: although the changes observed in the labor sphere have contributed to improvements in health and safety policies for, these changes have also contributed to the emergence of new risks arising from work activities, including psychosocial risks, which affect all occupational categories. Final considerations: we understand that the Brazilian Labor Reform carried out in 2017 leads to the weakening of labor relations, increases workers' exposure to risks in the workplace, increases the risk of illness, and opposes the global movement of international organizations aimed at the prevention of aggravation in workers' health and also at preserving their health.